Current perspective on retinal remodeling: Implications for therapeutics - Rebecca L. Pfeiffer; Bryan W. Jones (Frontiers in Neuroanatomy, 2022)
The retinal degenerative diseases retinitis pigmentosa and age-related macular degeneration are a leading cause of irreversible vision loss. Both present with progressive photoreceptor degeneration that is further complicated by processes of retinal remodeling. In this perspective, we discuss the current state of the field of retinal remodeling and its implications for vision-restoring therapeutics currently in development. Here, we discuss the challenges and pitfalls retinal remodeling poses for each therapeutic strategy under the premise that understanding the features of retinal remodeling in totality will provide a basic framework with which therapeutics can interface. Additionally, we discuss the potential for approaching therapeutics using a combined strategy of using diffusible molecules in tandem with other vision-restoring therapeutics. We end by discussing the potential of the retina and retinal remodeling as a model system for more broadly understanding the progression of neurodegeneration across the central nervous system.